Arquivos de Neuro-Psiquiatria: 75 years - Teive, Hélio A. Ghizoni; Caramelli, Paulo (Arquivos de Neuro-Psiquiatria, 2018)
This year marks the 75th year of publication of Arquivos de Neuro-Psiquiatria (ANP), the official journal of the Brazilian Academy of Neurology and one of the most important neuroscience journals in Latin America. ANP was initially edited by Oswaldo Lange, its founder, and subsequently by Antonio Spina-França Netto and, in recent years, by José Antonio Livramento and Luís dos Ramos Machado.
Keywords: neurology; history; brazilian Academy of Neurology, Arquivos de Neuro-Psiquiatria